The Effect of Direct Compensation and Work Motivation on Teacher Productivity at Private Senior High School in Jakarta - Ilham Kamaruddin; Hendy Tannady; Gamar Al Haddar; Darmawanta Sembiring; Ahmad Qurtubi (Edunesia: Jurnal Ilmiah Pendidikan, 2023)
Competition today among schools forces each school management to improve teacher performance by providing motivation, involving teachers in training, and providing compensation or bonuses to teachers who successfully carry out their duties properly. This research aims to know the effect of salary on teacher productivity and determine the effect of work motivation on teacher productivity. The type of research used in this research is quantitative. The quantitative research method can be interpreted as a research method based on the philosophy of positivism, used to examine specific populations or samples and collect data using research instruments. Data analysis is quantitative statistics to test established hypotheses. The research carried out by the authors in this study is by distributing questionnaires to teachers at SMA Della Strada North Jakarta. The results of this research show that salary and motivation have a positive and significant influence on teacher productivity.